THE PRINCIPLES OF LIABILITY ON TELEMEDICINE PRACTICES - Anwar, Arman (Pattimura Law Journal, 2016)
This research was aimed at analyzing and finding the principle of liability in telemedicine medical practice proportionally.This research is a legal research with the approach of statute approach, conceptual approach and comparative approach, as well as the approach to the case approach. According to Article 24 paragraph (1) of the 1945 Constitution and Article 5 (1) of Act No. 48 of 2009 on Judicial Authority, determine that the judge shall explore, and understand the legal values and sense of justice in society. Thus Article 1367 paragraph (3) BW and Article 46 of Act No. 44 of 2009 on Hospitals in the application must be in the context of the intended. The principle of liability risk in medical practice telemedicine in proportion refers to professional liability among medical practitioners telemedicine. The theoretical legitimacy is based on professional relationships in the delegation of medical action based on the code of ethics, professional standards, and service standards, and standard operating procedures. Consequences on liability does not necessarily have to be based on errors primary physician (primary care physician / PCP) or primary nurse as subordinate as mean vicarious liability doctrine. Nomenclature "proportional" in a significant liability risk as the distribution of rights and obligations of professionals in proportion to each party's fault based on the values of equality (equitability), feasibility and appropriateness (fair and reasionableness). Accountability based on the viewpoint of interactive justice according to the values of professional skill, prudence or accuracy, responsibility, and colleague and the desire to do good for the sake of healing patients (doing good).